Psalm 96: Israël en de volken - Beuken, Wim (Verbum et ecclesia, 1992)
Psalm 96: Israel and the Nations A text immanent reading of Psalm 96 reveals an unlimited salvation-universalism. Israel's experience that her God surpasses the gods of the nations in solicitude and power persuades her that she should make room for these nations by her side "in the presence of YHWH". Subsequently, this hospitality inspires Israel to prophetically proclaim YHWH’s kingship to these same nations. This confession does not only hold a guarantee for Israel herself but also offers certainty to the inhabitants of the world in their concern for the continued existence of the cosmos. Thus, side by side with the nations, Israel begins to share with them her expectation of the coming of YHWH as a hopeful prospect. God’s coming will not happen as a special favour for Israel but as a revelation of his faithfulness.